Global Burden of Type 1 Diabetes Mellitus Related Chronic Kidney Disease among Adolescents and Young Adults, and Projections to 2035: Results from the Global Burden of Disease Study 2021 - Xiaoli Qu; Chongbin Liu; Lin Sun; Zhifeng Sheng (Diabetes & Metabolism Journal)
Background Type 1 diabetes mellitus related chronic kidney disease (T1DM-CKD) presents a global health challenge, with unclear trends and patterns among adolescents and young adults. This study analyzed the burden and risk factors of T1DM-CKD in individuals aged 15 to 39 from 1990 to 2021 and predicted future trends. Methods Using data from the Global Burden of Disease (GBD) study 2021, we analyzed the prevalence, incidence, mortality, disability-adjusted life years (DALYs), and average annual percentage change (AAPC) of T1DM-CKD among youth across gender, sociodemographic index (SDI) areas, and data from 21 regions and 204 countries and territories. Risk factors were assessed and future trends were projected. Results Between 1990 and 2021, the global prevalence of T1DM-CKD aged 15 to 39 increased by 107.5% to 3.32 million, with an age-standardized prevalence rate (ASPR) of 111.44 per 100,000 (AAPC 1.33%). Incidence rose by 165.4% to 14,200, with an agestandardized incidence rate of 0.48 per 100,000 (AAPC 2.19%). However, age-standardized mortality rate (0.50 per 100,000, AAPC –0.87%) and age-standardized DALYs rate (30.61 per 100,000, AAPC –0.83%) decreased. ASPR increased across all SDI regions, especially in high-SDI countries. High fasting glucose remained the major risk factor influencing DALYs. By 2035, T1DM-CKD prevalence was projected to decrease to 2.86 million (ASPR 89.67 per 100,000). Conclusion The research revealed a global increase in T1DM-CKD among youth, with a shift towards younger onset and significant variations based on gender and location, emphasizing the importance of early prevention and management strategies for this demographic.